Adipose-derived mesenchymal stem cells combined with platelet-rich plasma are superior options for the treatment of osteoarthritis - Weijie He; Jie Zhao; Jiafei Liu; Fangxing Wang; Zhenyu Xu (Journal of Orthopaedic Surgery and Research)
Abstract Background There is currently no definitive treatment for osteoarthritis. We examined the therapeutic effects and underlying mechanisms of platelet-rich plasma (PRP) and adipose-derived mesenchymal stem cells (ADSCs), individually or in combination, in a rat model of anterior cruciate ligament-induced degenerative osteoarthritis (OA) of the knee. This study seeks to advance clinical approaches to OA treatment. Methods Eight- to nine-week-old male Sprague-Dawley (SD) rats were randomly assigned to two groups: (1) a normal control group (Group A) and (2) a model group. The control group received no treatment. The model group underwent treatment and was further subdivided into six groups: Group B (an injury control group), Group C (high-dose ADSCs), Group D (PRP combined with high-dose ADSCs), Group E (low-dose ADSCs), Group F (PRP combined with low-dose ADSCs), and Group G (PRP alone). PRP and/or ADSCs were administered via intra-articular injection on Days 7, 37, and 67 post-surgery. Daily observations recorded activity levels and behavior, while weight changes were monitored weekly. Digital radiography (DR) was conducted on Days 30, 60, and 90 post-surgery to assess joint surface and contour alterations. Histopathological examination and inflammatory factor analysis were performed on cartilage and synovial tissue. Results No abnormal reactions were observed in any rats, and body weights increased as expected (P > 0.05). Significant differences in knee swelling rates and Wakitani scores were observed between Groups A and B (P < 0.01). Knee swelling rates also differed significantly between Group B and Groups C–G (P < 0.01). Wakitani scores decreased on Days 60 and 90 in Groups C–G. TNF-α and IL-1β expression levels were significantly higher in Group B compared to Group A (P < 0.05). Expression levels of these genes were significantly lower in Groups C–G than in Group B (P < 0.05). Conclusions Repeated intra-articular injections of PRP and ADSCs alleviated inflammation and pain, promoted tissue repair, and modulated immune responses in rats with surgically induced OA. The combination of PRP and ADSCs demonstrated enhanced therapeutic efficacy, suggesting its potential as a treatment option for OA.